Higher Education during Lockdown: Literature Review and Implications on Technology Design - Laato Samuli; Farooq Ali; Vilppu Henna; Airola Antti; Murtonen Mari (HINDAWI LTD, 2022)
Countries globally reacted to the COVID-19 pandemic by imposing lockdowns, and as a consequence, higher education institutions were forced to rapidly transition into distance learning. Here, technology played a paramount role as the enabler of remote learning and shaping teaching practices. The aim of this study is to understand the broad trends in higher education during the early lockdown transitions and the role of technology in this process through a literature review approach. After searching for literature and applying inclusion and exclusion criteria, 61 relevant publications were discovered, which were sorted into three clusters using co-word analysis: (1) teaching and learning; (2) policy and managerial issues; and (3) students' psychological well-being. Each theme was further divided into subthemes based on a thematic clustering approach. Based on this review, implications on learning technology design during the time of a pandemic were derived. First, due to the lack of social contacts resulting from isolation measures, emphasis is needed on interstudent interaction. Second, mobile distance learning technologies and teaching methods could be designed to enable students to move or exercise while learning. Third, diverse pedagogical approaches should be looked into to bring variety into students' lives.